Hematite Photoanodes Modified with an FeIII Water Oxidation Catalyst. Issue 6 (18th March 2014) - Dalle Carbonare, Nicola; Cristino, Vito; Berardi, Serena; Carli, Stefano; Argazzi, Roberto; Caramori, Stefano; Meda, Laura; Tacca, Alessandra; Bignozzi, Carlo Alberto
Abstract Hematite photoelectrodes prepared via a hydrothermal route are functionalized with a water oxidation catalyst consisting of amorphous FeIII oxide, obtained by successive ionic layer adsorption and reaction. The performances of the catalyst‐modified photoanodes are considerably higher than those of the parent electrodes, resulting in a nearly doubled photoanodic current in all the basic aqueous electrolytes explored in this study. The combination of electrochemical impedance spectroscopy and laser flash photolysis indicates that the presence of the catalyst results in enhanced hole trapping in surface reactive states exposed to the electrolyte, allowing for a more successful competition between charge transfer and recombination.